Sizing photovoltaic systems interconnected to the grid in the industry - Raúl García García; G. Orozco Gamboa; Marco Antonio Zamora Antuñano; Marisela Cruz Ramírez; Saturnino García García; Lourdes Vital López; Eyra Liliana Ortiz Pérez (Maejo International Journal of Energy and Environmental Communication, 2021)
Renewable energy sources have been regarded as the best alternative for energy generation because they are environmentally friendly and can be renewed. Among the sources of renewable energy is the photovoltaic system. The generation of energy through clean energies such as photovoltaic systems connected to the grid have shown sustained growth for years in residences, commercial centers, and industry. Therefore, a practical study of a photovoltaic system connected to the grid of a specific industry in the San Juan del Río region was carried out to determine the effectiveness and the cost efficiency of running a photovoltaic system connected to a grid. We also investigated the fastest possible time to get return on investment. The return on investment was estimated using the peak solar hours, numbers of panels, inverter, conductors, and DC and AC protectors. Although, the cost of starting a photovoltaic system can be quite expensive, our analysis revealed that the return on the investment can start to come to effect within a very short period. The policy implication of this is that the government should encourage investment on the photovoltaic system through financial support to firm and other policies that can make delivery cheaper for the customers.